A Study of improving the Capacity of Teachers Working in the Vocational Education System and Training Centers: Challenges and Opportunities in Improving Vocational Education for Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Vocational training in industries like manufacturing or construction is a crucial component ofour educational strategy. If vocational education is to play an effective role in the rapidly changingnational environment and reap the demographic dividend in India, it is imperative that it provide flexible,current, relevant, inclusive, and innovative vocational education and training. The government hasalready taken a number of significant steps in this direction and acknowledges the crucial role thatvocational education will play in the future of the nation. Population for this study was teachers andtrainers of the vocational training centers in DelhiNCR region comprised in the research. A small portionof chosen population, more particularly the teachers, dealt to some degree of negligence where thesurvey forms are filled out. There was the use of cross-sectional research design so one can choosevocational education schools and teachers in a random order. Here 500 respondents were the finalsample size in research. Investigator selected 500 students as sample from 20 schools 10 is governmentschool and 10 is private school in located at South Delhi where Vocational Education were imparted.The questionnaire exclusively prepared by the Investigator for the students of such schools wasadministered on the sample to know the status and problems faced by them. The questionnaire wasdeveloped in English. It has 15 items of both open-ended and closed ended. The responses to openendeditems have been grouped and frequencies obtained